2011
DOI: 10.1366/11-06310
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Drugs of Abuse in Saliva by Surface-Enhanced Raman Spectroscopy (SERS)

Abstract: Eighty drugs of abuse and metabolites were successfully measured by surface-enhanced Raman spectroscopy (SERS) using gold- and silver-doped sol-gels immobilized in glass capillaries. A method was developed that provided consistent detection of 50 ppb cocaine in saliva in a focused study. This general method was successfully applied to the detection of a number of additional drugs in saliva, such as amphetamine, diazepam, and methadone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
104
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 14 publications
2
104
0
1
Order By: Relevance
“…Various methods have been utilized to measure glucose in vivo, 68 to immunolabel cancer cells, 69 to isolate and identify bacteria from blood infections, 70 and to detect drugs in saliva. 71 We will briefly describe a few of these applications, which we believe serve as good examples of the general sub-field. It has been found that certain molecules (those that are most easily capable of single molecule SERS) produce an extraordinarily large Raman enhancement in SERS.…”
Section: Light Scattering By Metal Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods have been utilized to measure glucose in vivo, 68 to immunolabel cancer cells, 69 to isolate and identify bacteria from blood infections, 70 and to detect drugs in saliva. 71 We will briefly describe a few of these applications, which we believe serve as good examples of the general sub-field. It has been found that certain molecules (those that are most easily capable of single molecule SERS) produce an extraordinarily large Raman enhancement in SERS.…”
Section: Light Scattering By Metal Nanoparticlesmentioning
confidence: 99%
“…77,78 In recent years, there have been a large number of explored biomedical applications that utilize SERS as a source of contrast. These applications range from isolated and detecting bacteria in blood for the purpose of improving the treatment of sepsis patients, 70 identifying proteins, 67 monitoring of blood glucose levels, 68 and detecting drugs in body fluids, 71,79 to name a few. The large amount of interest in the development of SERS techniques and their biomedical applications is a strong indicator of the vast potential of the phenomenon.…”
Section: Light Scattering By Metal Nanoparticlesmentioning
confidence: 99%
“…Researchers have abtained SERS spectra of amphetamine, diazepam and methadone in saliva, 26 Clement Yuen 27 detected paclitaxel in blood plasma by SERS with a rather technically prepared substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, silver or gold nanostructured surfaces are used to enhance Raman spectra of molecules, with a sensitivity that reaches single‐molecule levels 4. This high sensitivity also makes it applicable in, for example, forensic trace detection5 or biomolecular assays 6. As SERS is highly confined to the metal surface, it allows for the selective study of the molecules in close proximity to the surface.…”
mentioning
confidence: 99%